2023
DOI: 10.3389/fped.2023.1060053
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of immunological events in Epstein-Barr virus infection in children with infectious mononucleosis

Abstract: Backgrounds & aimsEpstein-Barr virus (EBV) infection occurs commonly in children and may cause acute infectious mononucleosis (AIM) and various malignant diseases. Host immune responses are key players in the resistance to EBV infection. We here assessed the immunological events and laboratory indicators of EBV infection, as well as determined the clinical usefulness of evaluating the severity and efficacy of antiviral therapy in AIM patients.MethodsWe enrolled 88 children with EBV infection. The immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Studies on the molecular diversity of EBV in IM are of particular importance in the more detailed characterization of innate and specific immune responses to EBV, the fundamental immunobiology of EBV infection as well as in the development of prophylactic and therapeutic vaccines [ 50 , 51 , 52 ]. The recently described role of EBV as a co-factor in the development of multiple sclerosis has renewed the interest in the development of prophylactic based on mRNA technology [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the molecular diversity of EBV in IM are of particular importance in the more detailed characterization of innate and specific immune responses to EBV, the fundamental immunobiology of EBV infection as well as in the development of prophylactic and therapeutic vaccines [ 50 , 51 , 52 ]. The recently described role of EBV as a co-factor in the development of multiple sclerosis has renewed the interest in the development of prophylactic based on mRNA technology [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study by Rajendran et al (2016) demonstrated that ectopic CD137 expression on HRS cells enables the secretion of IL-13, facilitating immune escape by reducing IFNγ [ 180 ]. Decreases in IFN- γ secretion by cytokoxic T lymphocytes were observed in a recent study by Zhang et al (2023) in children with infectious mononucleosis [ 181 ]. On the other hand, Lambert et al 2007 demonstrated for the first time that the induction of IL-10 by LMP1 in B cells is not only p38-dependent but also uses the PI3K/Akt pathway [ 84 ].…”
Section: Ebv-mediated Induction Of Immunomodulatory Molecules By Acti...mentioning
confidence: 96%
“…For severe acute respiratory syndrome coronavirus 2(SARS-CoV-2) infection, severe cases more frequently had dyspnea, lymphopenia, and hypoalbuminemia, with higher levels of alanine aminotransferase(ALT), lactate dehydrogenase, C-reactive protein, ferritin, and D-dimer as well as markedly higher levels of IL-2R, IL-6, IL-10, and TNF-α [ 11 ]. For Epstein-Barr virus(EBV) infection, aspartate aminotransferase(AST) level, number of CD8 + T cells, and CD62L expression on T cells were related to the severity of infectious mononucleosis [ 12 ]. For ADV infection, more data on co-infection were reported, for example human ADV type 7 and invasive pulmonary fungal co-infection [ 13 ], mycoplasma pneumoniae(MP) and ADV co-infection [ 14 ] and so forth.…”
Section: Introductionmentioning
confidence: 99%